2023
DOI: 10.1111/bjh.19075
|View full text |Cite
|
Sign up to set email alerts
|

Refractory immune thrombocytopenia in adults: Towards a new definition

Donald M. Arnold,
Bianca Clerici,
Ekaterina Ilicheva
et al.

Abstract: SummaryImmune thrombocytopenia (ITP) is an autoimmune haematological disorder characterized by immune‐mediated thrombocytopenia and a variable risk of bleeding. Despite the availability of multiple treatment options, some patients are considered refractory since they do not achieve a platelet count response to multiple treatments and are at risk of bleeding. The term ‘refractory’ has been used to identify this patient group; however, with the advent of multiple lines of treatment, its meaning has become ambigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They reported that the threshold value to identify a “low” platelet count is variable, depending on the patient’s age, comorbidities, and concomitant therapies (e.g., antiplatelet or anticoagulant agents) [ 116 ]. In 2023, Arnold DM et al proposed the following definition of refractory ITP for consideration and future evaluation: persistence of severe thrombocytopenia (platelets < 20 × 10 9 /L) and bleeding in a patient with ITP who has received rituximab, two different TPO-RAs, and at least one immunosuppressant medication and who does not respond or only briefly responds to high-dose corticosteroids or high-dose IVIGs (less than 7 days) [ 117 ].…”
Section: Refractory Itpmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the threshold value to identify a “low” platelet count is variable, depending on the patient’s age, comorbidities, and concomitant therapies (e.g., antiplatelet or anticoagulant agents) [ 116 ]. In 2023, Arnold DM et al proposed the following definition of refractory ITP for consideration and future evaluation: persistence of severe thrombocytopenia (platelets < 20 × 10 9 /L) and bleeding in a patient with ITP who has received rituximab, two different TPO-RAs, and at least one immunosuppressant medication and who does not respond or only briefly responds to high-dose corticosteroids or high-dose IVIGs (less than 7 days) [ 117 ].…”
Section: Refractory Itpmentioning
confidence: 99%
“…Although it was traditionally considered that 20% of patients do not achieve an adequate platelet count after splenectomy or after initial and subsequent medical treatment [ 13 ], nowadays, this percentage is probably much lower and difficult to estimate due to the lack of current consensus for the definition of refractoriness. Preliminary data from the McMaster and Norwegian ITP registries demonstrate that the proportion of adult ITP patients who have received first-line therapy, rituximab, at least one TPO-RA, and splenectomy ranges from 3.1% to 4.7% [ 117 ].…”
Section: Refractory Itpmentioning
confidence: 99%